DESENVOLVIMENTO E CARACTERIZAÇÃO DE BIOPRODUTOS ORIUNDOS DE Fridericia platyphylla (CHAM.) L.G. LOHMANN ATUANDO EM LEISHMANIOSE - NEVES, Mônica Araujo das (2025)
Leishmaniasis is a neglected parasitic disease caused by protozoa of the Leishmania genus, representing a serious global public health problem. Available therapies are limited to a few drugs, such as meglumine antimoniate, amphotericin B, and miltefosine, all associated with high toxicity, high costs, and increasing parasite resistance. In this context, the search for new bioactive compounds with greater selectivity and lower toxicity becomes essential. This study presents the first evidence that brachydins present in the dichloromethane fraction (FDCM) of Fridericia platyphylla inhibit the triosephosphate isomerase (TIM) enzyme of Leishmania, affecting its stability and catalytic function. This discovery opens new perspectives for understanding the molecular mechanisms of leishmaniasis and developing new drugs. Experimentally, FDCM exhibited inhibitory activity against promastigotes of L. infantum, L. braziliensis, and L. mexicana, with IC₅₀ values of 10.13, 11.44, and 11.16 µg/mL, respectively, and against intracellular amastigotes of L. infantum (IC₅₀ = 4.81 µg/mL). Furthermore, it demonstrated a moderate cytotoxicity profile for RAW264.7 macrophages (CC₅₀ = 25.15 µg/mL), with a selectivity index (SI = 5.2), higher than that of meglumine antimoniate (SI = 2.7) but lower than that of amphotericin B (SI = 41.5), suggesting a viable therapeutic potential. To optimize its pharmaceutical application, FDCM was encapsulated in zein polymeric nanoparticles (NPZ-FDCM) and poly(- caprolactone) nanoparticles (NPCL-FDCM). NPZ-FDCM showed high encapsulation efficiency (~99%), homogeneous size distribution, and stability for 49 days, along with a suitable zeta potential for colloidal stability. In the anti-leishmanial assay, NPZ-FDCM demonstrated greater efficacy against amastigote forms of L. amazonensis (IC₅₀ = 0.72 µg/mL), whereas NPCL-FDCM did not exhibit significant activity at the tested concentration. The findings of this study highlight FDCM as a promising alternative to conventional drugs, combining high selectivity, lower toxicity, and reduced environmental impact. Encapsulation in zein nanoparticles enhances its efficacy, reinforcing its potential as an innovative candidate for leishmaniasis treatment.